2004
DOI: 10.1158/1078-0432.ccr-03-0988
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Assessment of the Peripheral Benzodiazepine Receptor in Breast Cancer and Its Relationship with Survival

Abstract: As the axillary lymph node-negative status is generally considered as a good prognosis factor, the high expression of PBR in this patient subgroup may be used to identify a new high risk population, for which a more specific therapy would be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 20 publications
3
91
2
5
Order By: Relevance
“…HR associated with Ki-67 positivity in this case) from studies with inherent dissimilarities. The observed disparity among the conclusions of different studies, responsible for the observed heterogeneity, can be quantified by applying Bukholm et al (2003) 147 No Ceccarelli et al (2000) 217 Yes Galiegue et al (2004) 117 No Gasparini et al (1992) 164 Yes Haerslev et al (1996) 487 Yes Jalava et al (2000) 414 No Kroger et al (2006) 157 No Kronblad et al (2006) 377 Yes Lampe et al (1998) 142 Yes Liu et al (2000) 225 Yes Michels et al (2003) 104 No Molino et al (1997) 322 Yes Rudas et al (1994) 184 No Tsutsui et al (2005) 249 Yes Yang et al (2003) 147 No…”
Section: Discussionmentioning
confidence: 99%
“…HR associated with Ki-67 positivity in this case) from studies with inherent dissimilarities. The observed disparity among the conclusions of different studies, responsible for the observed heterogeneity, can be quantified by applying Bukholm et al (2003) 147 No Ceccarelli et al (2000) 217 Yes Galiegue et al (2004) 117 No Gasparini et al (1992) 164 Yes Haerslev et al (1996) 487 Yes Jalava et al (2000) 414 No Kroger et al (2006) 157 No Kronblad et al (2006) 377 Yes Lampe et al (1998) 142 Yes Liu et al (2000) 225 Yes Michels et al (2003) 104 No Molino et al (1997) 322 Yes Rudas et al (1994) 184 No Tsutsui et al (2005) 249 Yes Yang et al (2003) 147 No…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TSPO has also been observed in breast cancer cell lines (139) and in clinical studies (140). In the former, estrogen receptor-negative breast cancer cell lines had significantly higher TSPO expression compared to ER-positive lines and the levels of TSPO were positively correlated with the proliferation marker, Ki-67 (139).…”
Section: Tspo In Cellular and Tissues Pathologymentioning
confidence: 90%
“…This observation was mirrored in the clinical study in which TSPO expression was significantly increased in tumoral versus normal breast cells and TSPO was again correlated with Ki-67 levels. TSPO was anyway never associated with reduced prognosis in the whole patient sample, but in lymph-node negative group of patients, elevated TSPO was linked to a shorter disease-free survival period, indicating that TSPO could be used to identify a higher risk population in this category (140). TSPO is reported overexpressed in oesophageal cancer cells compared to normal oesophageal epithelium (141), as well as in human endometrial carcinoma, where significantly more mitochondrial TSPO was observed in contrast to normal endometrium (142).…”
Section: Tspo In Cellular and Tissues Pathologymentioning
confidence: 95%
“…20,52 In whole-cell assays, specific PK11195 binding can vary more than 20-fold in primary AML cell samples and is frequently higher in AMLs than in normal bone marrow cells (Walter et al 21 and data not shown). Cells from ovary, liver, colon, breast, and brain tumors also express dramatically higher levels of pBR relative to normal cells of the same tissue origin (eg, Galiegue et al 60 ). Because we have shown that increased pBR expression can increase the degree to which PK11195 chemosensitizes transporterdeficient cancer cells, PK11195 binding data may have prognostic value for PK11195 clinical applications aimed at promoting mitochondrial-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%